The Influence of Good Corporate Governance on Financial Distress with Capital Structure as a Moderating Variable - Hafidz, Ahmad Ridho; Lestari, Yona Octiani (Universitas Gorontalo, 2025)
This study aims to determine the effect of Good Corporate Governance on Financial Distress with Capital Structure as a moderating variable. The population in this study were all Islamic Commercial Banks registered with the Financial Services Authority (OJK) in the 2014-2022 period and the sample was determined using Purposive Sampling Technique. The data analysis technique used is Multiple Linear Regression and Moderation Regression. The results of the study indicate that partially only the Size of the Sharia Supervisory Board and the Composition of Independent Commissioners have a significant negative effect on Financial Distress, while in contrast to Company Size which shows a significant positive effect on Financial Distress. However, Capital Structure is not able to moderate the relationship between Good Corporate Governance and Financial Distress.